The Meaning of Childfree for Unmarried Women Reviewed from The Perspective of Symbolic Interaction Theory - Fauzia, Irma; Mony, Husen (P3M Politeknik Negeri Media Kreatif, 2023)
The study has been done to know the meaning, background, and self-concept of millennials women's who not married. This kind of study is qualitative by interview, observation, and be completed by references. The theory which the study used is symbolic interaksionism by Herbert Blume who delevop from George Herbert Mead's. Symbolic interactionism focuses on the relationships among individuals within a society which create a meaning become a symbol, s the symbols will have a meaning. The result of study shows the meaning of childfree based on the individual relationships on society, which is their parent, especially a mother. This thing built by the individual communications with them, which created their self-concept then make a meaning of childfree